Use of basalt powder in a cementitious mortar and concrete as a substitute of sand - Dobiszewska, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The present study shows the results of the possibility of using basalt powderin cementitious mortar and concrete. Asphalt mixture production leads to formation of significant amounts of mineral powder. It is used in a present research. Utilization of this waste is a problem in Asphalt Batch Mix Plant. Experiments were carried out to determine an influence of powder basalt on some properties of cementitious mortar. The compressive and flexural strength at 2, 28 and 56 days of curing, freeze resistance, absorptivity, capillary rise of water and softening factor were conducted. Thermal conductivity factor was determined by means of Thermal Conductivity Measuring Instrument TCA 300 to assess a thermal insulation parameters of mortars. Secondly, experiments were also carried out to determine an influence of addition of powder basalt on some properties of concrete. The compressive strength at 28, 90, 180 days of curing and freeze resistance were conducted. Cementitious mortars and concrete were prepared with powder basalt as a partial substitute of sand in amount of 0-30% and 0-20% sand mass respectively. The results show that powder basalt can be use as an effective substitute of fine aggregate in cementitious mortar and concrete. Use of the powder basalt as a partial substitution of sand improves some properties of cementitious mortar and concrete and anable for the management of industrial waste.